2012
DOI: 10.1515/jpem-2012-0253
|View full text |Cite
|
Sign up to set email alerts
|

A decrease in fasting FGF19 levels is associated with the development of non-alcoholic fatty liver disease in obese adolescents

Abstract: A decrease in fasting FGF19 is associated with the development of NAFLD in obese adolescents. A decrease in fasting FGF19 levels may be a new important risk factor for NAFLD and the metabolic syndrome in adolescents. Further studies are needed to explain whether exogenous delivery of FGF19 might be therapeutically beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 0 publications
8
62
1
1
Order By: Relevance
“…Here, a number of reports consistently found decreased fasting FGF19 levels in patients with either of these entities [71][72][73][74][75][76]. One study also suggests an inverse correlation of serum FGF19 with disease progression (in terms of NASH and fibrosis) in children with biopsy-proven NAFLD [77].…”
Section: Metabolic Disordersmentioning
confidence: 61%
“…Here, a number of reports consistently found decreased fasting FGF19 levels in patients with either of these entities [71][72][73][74][75][76]. One study also suggests an inverse correlation of serum FGF19 with disease progression (in terms of NASH and fibrosis) in children with biopsy-proven NAFLD [77].…”
Section: Metabolic Disordersmentioning
confidence: 61%
“…Nevertheless, additional analysis performed in our study showed lower concentration level of the fibroblast growth factor 19 (FGF19) in patients with hypovitaminosis D. Fibroblast growth factor 19 (FGF19) is a hormone released from the small intestine; recently, it has emerged as an endocrine regulator of glucose and lipid metabolism. The results of the presented study, although not statistically significant, need particular attention, since a decrease in fasting FGF19 is an independent risk factor for the development of NAFLD in obese adolescents [23,24,25]. Its relationship to vitamin D deficiency needs further investigation.…”
Section: Meanmentioning
confidence: 64%
“…Fgf15 knockout mice showed glucose intolerance, increased hepatic gluconeogenesis, and reduced hepatic glycogen storage but unaltered overall insulin sensitivity. Decreased fasting FGF19 levels or impaired hepatic response to FGF19 have been reported in humans with fatty liver and insulin resistance (Schreuder et al, 2010;Wojcik et al, 2012). These studies suggest that bile acid regulation of hepatic glucose metabolism involves complex cross-talk between FXR-dependent pathways and FXR-independent signaling pathways.…”
Section: Bile Acid Receptor Signaling In Liver Metabolismmentioning
confidence: 74%